2013
DOI: 10.1007/978-3-642-39637-3_19
|View full text |Cite
|
Sign up to set email alerts
|

An Ontological Approach to Meet Information Needs of Farmers in Sri Lanka

Abstract: Abstract. Farmers in Sri Lanka are badly affected by not being able to get vital information required to support their farming activities in a timely manner. Some of the required information can be found in government websites, agriculture department leaflets, and through radio and television programs on agriculture. Due to its unstructured and varied format, and lack of targeted delivery methods, this knowledge is not reaching the farmers. Therefore, this knowledge needs to be provided not only in a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…To clearly identify the process of the ontology development to represent the information in user context, this section (section II) is mainly organized in six (6) categories such as users' information needs, users' information needs in context, representation of contextualized information, generalizing design approach, and validation and evaluation process. The framework we identified to maintain the ontology for our application is described separately in section III.…”
Section: Ontology Development Processmentioning
confidence: 99%
See 3 more Smart Citations
“…To clearly identify the process of the ontology development to represent the information in user context, this section (section II) is mainly organized in six (6) categories such as users' information needs, users' information needs in context, representation of contextualized information, generalizing design approach, and validation and evaluation process. The framework we identified to maintain the ontology for our application is described separately in section III.…”
Section: Ontology Development Processmentioning
confidence: 99%
“…Some examples are given in Table I. In this study we identified that, farm environment, types of farmers, farmers' preferences, and farming stages (considered as the user context model) are the important factors that need to be considered when delivering agricultural information and knowledge to farmers [6].…”
Section: A Users' Information Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a combination of different content, information applications, and systems across Internet [6]. Therefore, data management of semantic web should be done in efficient method.…”
Section: Introductionmentioning
confidence: 99%